DIAGNOSTIC ACCURACY OF RIPASA SCORE FOR DIAGNOSING ACUTE APPENDICITIS KEEPING HISTOPATHOLOGY AS GOLD STANDARD - KHAN , A; MUMTAZ , N; MALIK , AH; KHAN , SU; GUL , A; ASMAT , S; AMIN , F (Biological and Clinical Sciences Research Journal, 2023)
The objective of the study was to determine the diagnostic accuracy of the RIPASA score in diagnosing acute appendicitis using histopathology as the gold standard. The cross-sectional study was conducted at the General Surgery Department of Lady Reading Hospital, Peshawar, between 17-03-2020 and 16-092020. A total of 171 patients were enrolled in the study. Each patient underwent the RIPASA score, followed by an appendectomy. The appendix specimen obtained during the appendectomy was sent to the laboratory for histopathology. After receiving the histopathology study’s objective, which was to determine the report, the results of histopathology, RIPASA score, and other information, including name, age, gender, and age group, were recorded. The age distribution in the sample varied from 15-65 years, with a mean age of 25.8±11.0 years. There were 114 males (66.7%) and 57 females (33.3%). The RIPASA score had a sensitivity of 94.9%, specificity of 64.2%, PPV of 96.7%, NPV of 52.9%, and accuracy of 92.4%. Stratification was also carried out for age and gender. Age 15-25 showed a sensitivity of 94%, specificity of 57.1%, PPV of 97.3%, NPV of 36.3%, and accuracy of 91.9%. Similarly, the age 26-65 group revealed a sensitivity of 97.5%, specificity of 71.4%, PPV of 65.1%, NPV of 83.3%, and accuracy of 93.6%. Stratification by gender showed a sensitivity of 94.2%, specificity of 66.6%, PPV of 97%, NPV of 50%, and accuracy of 92.1% for males, while for females, the sensitivity was 96.1%, specificity was 60%, PPV was 96.1%, NPV was 60%, and accuracy was 92.9%. In conclusion, the study suggests that the RIPASA scoring system is a good choice for doctors in the emergency department to aid in diagnosing acute appendicitis with good sensitivity, albeit with a slightly high profile and specificity, albeit with a bit low profile.